Giant Rashba effect at the topological surface of PrGe revealing antiferromagnetic spintronics - Banik, Soma (Sci Rep, 2017)
Rashba spin-orbit splitting in the magnetic materials opens up a new perspective in the field of spintronics. Here, we report a giant Rashba spin-orbit splitting on the PrGe [010] surface in the paramagnetic phase with Rashba coefficient α (R) = 5 eVÅ. We find that α (R) can be tuned in this system as a function of temperature at different magnetic phases. Rashba type spin polarized surface states originates due to the strong hybridization between Pr 4f states with the conduction electrons. Significant changes observed in the spin polarized surface states across the magnetic transitions are due to the competition between Dzyaloshinsky-Moriya interaction and exchange interaction present in this system. Presence of Dzyaloshinsky-Moriya interaction on the topological surface give rise to Saddle point singularity which leads to electron-like and hole-like Rashba spin split bands in the [Formula: see text] and [Formula: see text] directions, respectively. Supporting evidences of Dzyaloshinsky-Moriya interaction have been obtained as anisotropic magnetoresistance with respect to field direction and first-order type hysteresis in the X-ray diffraction measurements. A giant negative magnetoresistance of 43% in the antiferromagnetic phase and tunable Rashba parameter with temperature makes this material a suitable candidate for application in the antiferromagnetic spintronic devices.